Disease burden and long-term trends of urinary tract infections: A worldwide report - Yang, Xiaorong; Chen, Hui; Zheng, Yue; Qu, Sifeng; Wang, Hao; Yi, Fan (Frontiers in Public Health, 2022)
Background: Urinary tract infections (UTIs) are one of the most common infections worldwide, but little is known about their global scale and long-term trends. We aimed to estimate the spatiotemporal patterns of UTIs burden along with its attributable risk factors at a global level, as well as the variations of the burdens according to socio-demographic status, regions, nations, sexes and ages, which may be helpful in guiding targeted prevention and treatment programs. Methods: Data from the Global Burden of Disease Study 2019 were analyzed to depict the incidence, mortality, and disability-adjusted life years (DALYs) of UTIs in 204 countries and territories from 1990 to 2019 by socio-demographic status, nations, region, sex, and age. Results: Globally, 404.61 million cases, 236,790 deaths and 520,200 DALYs were estimated in 2019. In particular, 2.4 times growth in deaths from 1990 to 2019 was observed, along with an increasing age-standardized mortality rate (ASMR) from 2.77/100,000 to 3.13/100,000. Age-standardized incidence rate (ASIR) was consistently pronounced in regions with higher socio-demographic index (SDI), which presented remarkable upward trends in ASMR and age-standardized DALY rate (ASDR). In contrast, countries with a low SDI or high baseline burden achieved a notable decline in burden rates over the past three decades. Although the ASIR was 3.6-fold higher in female than male, there was no sex-based difference in ASMR and ASDR. The burden rate typically increased with age, and the annual increasing trend was more obvious for people over 60 years, especially in higher SDI regions. Conclusions: The burden of UTIs showed variations according to socio-demographic status, nation, region, sex, and age in the last three decades. The overall increasing burden intimates that proper prevention and treatment efforts should be strengthened, especially in high-income regions and aging societies.